2023
DOI: 10.1109/access.2023.3277196
|View full text |Cite
|
Sign up to set email alerts
|

AC Loss Reduction in HTS Coil Windings Coupled With an Iron Core Using Flux Diverters

Abstract: Iron cores are widely employed in high temperature superconducting (HTS) power devices to enhance the magnetic field and improve the power density. In spite of these benefits, the presence of iron cores leads to a substantial increase in AC loss within HTS coil windings. Therefore, it is necessary to estimate the AC loss of HTS coil windings coupled with iron cores to propose methods for loss reduction. An effective way to reduce AC loss is to apply flux diverters (FDs) near the HTS coil windings. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Several numerical and experimental studies on the influence of ferromagnetic materials in AC loss of HTS tapes, stacks, and coil windings have been conducted [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Previous numerical works based on the finite element method (FEM) have shown that iron cores influence the AC loss of HTS coil assemblies [26][27][28][29][30][31][32]. For single pancake coils coupled with iron cylinders, AC loss simulations have implied that the incorporation of iron cores slightly increased coil AC losses [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several numerical and experimental studies on the influence of ferromagnetic materials in AC loss of HTS tapes, stacks, and coil windings have been conducted [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Previous numerical works based on the finite element method (FEM) have shown that iron cores influence the AC loss of HTS coil assemblies [26][27][28][29][30][31][32]. For single pancake coils coupled with iron cylinders, AC loss simulations have implied that the incorporation of iron cores slightly increased coil AC losses [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…For single pancake coils coupled with iron cylinders, AC loss simulations have implied that the incorporation of iron cores slightly increased coil AC losses [29,30]. On the other hand, the simulated AC loss value of a coil winding comprised of a stack of 8 DPCs coupled with an iron core is one order of magnitude greater than that without the iron core [31,32].…”
Section: Introductionmentioning
confidence: 99%